AGAP: an atmospheric gondola for aerosol profiling - Mazzola, M; Busetto, M; Viola, A; Cappelletti, D.; FERRERO, LUCA (Rendiconti Lincei, 2016)
A novel airborne gondola was developed to profile the Arctic boundary layer exploiting a tethered balloon system. A number of aerosol instrumentations were customized and deployed in the gondola for two test campaigns conducted in Ny-Ålesund in September 2014 and April–May 2015. The performances of the instrumental setup have been characterized and will be described in the present paper. An illustration of the main results and a discussion of the main phenomenology will be also presented. Briefly, the tethered balloon systems demonstrates the capability of successfully lifting up to 15 kg of scientific payload, featuring a power autonomy of about 3 h of continuous measurements with one battery. We demonstrate for the first time on a tethered balloon the capability of measuring at the same time aerosol light scattering, absorption coefficients and size distribution, which is very promising for deducing the aerosol optical properties as a function of height along the probed atmospheric column.